Determinantes principais de inovaç\~ao na indústria brasileira: Uma análise preliminar - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper investigates whether global sourcing is significant as a causative factor to explain innovation in the Brazilian industry. The main conclusion is that this factor is important only in the scale intensive industrial sectors. Besides the National Innovation System seems to be weak and without strong effect as a Brazilian innovation determinant.
Keywords: D21; L10; 330